Case Report: Independence day, comparison of methods to estimate the onset of dispersal in large territorial birds - Diego Gallego-García; Bryan D. Watts; José Hernán Sarasola (Animal Biotelemetry)
Abstract Background In birds, the onset of dispersal is the transition point between the end of the post-fledging dependence period (PFDP) and the beginning of natal dispersal. Identifying this key moment in an individual’s life cycle is crucial for understanding the ecology and demography of a species, but its determination remains a challenge. Some methodologies used to estimate it usually yield biased outcomes, while others are based on adult ranging areas and require previous knowledge on the species’ movement patterns, precluding their use in little-known species. Additionally, the proposed methods have never been compared with data on family breakup timing. Thus, creating a standardized methodology, not based on species-specific information and with a reliable reference, to estimate the onset of dispersal for its use on a wider array of birds is key to optimizing research on rare and/or elusive species. Methods We used unique GPS data from parent Chaco eagles (Buteogallus coronatus), a large, territorial, and endangered species, with their corresponding fledglings during the PFDP as a reference against which to evaluate (1) the existing methodologies in the literature; (2) modified methods based on previous ones; and (3) new methods related to changes and overlap values in the ranging areas of young individuals. To quantitatively assess which method best matched the reference values, we calculated the mean deviation and bias on an individual basis, also accounting for the interindividual coefficient of variation. Results Most previously published methods assign the onset of dispersal prematurely, probably because they are sensitive to exploratory or foraging movements that young individuals perform prior to dispersal. The modified methods, although more accurate, still provided biased estimates. However, the new methods we propose provided estimates of the onset of dispersal with increased accuracy and low interindividual variability. Conclusions The new methods proposed (1) provide the most accurate estimates of the onset of dispersal; (2) are standardized, so they can be used for a wide range of bird species; (3) do not require previous knowledge of adult movement patterns; and (4) are very useful for most bird research studies that tag fledglings with GPS transmitters.